Diagnosis of the Non-Concurrent Operation of the On-Load Tap Changer Contacts by the Acoustic Emission Method - CICHOŃ, Andrzej; BORUCKI, Sebastian; BOCZAR, Tomasz (Archives of Acoustics, 2011)
On-load tap changers (OLTC) are some of the main transformer elements thatmake voltage adjustment in a power network possible. Their failures often causeshutdowns of distribution transformers. The paper presents research work aimedat the assessment of the technical condition of OLTCs by the acoustic emissionmethod (EA). This method makes the OLTC diagnosis possible without the needof disconnecting the transformer from the system. The measurements were takenin laboratory conditions. The influence on the operation non-concurrence of thepower tap changer contacts on the AE registered signals has been investigated. Thesignals registered were subjected to analyses in the time and time-frequency do-mains. The result analysis in the time domain was carried out using the Hilberttransform and calculating characteristic times for the particular runs. A short-timeFourier transform was used for the assessment of results in the time-frequency do-main.